Analysis of Market Structure and Performance of the Textile and Textile Products (TPT) Industry in Indonesia: Structure-Behavior-Performance Approach - Siahaan, Karin Sarah Angelina; Manalu, Maria Elpida; Aqiila, Rifka; Ruslan, Dede (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
One important variable used to measure performance in structure-behavior-performance analysis is profit (Price Cost Margin/PCM). The more concentrated an industry is (higher CR4), the higher the profits of existing firms will be. This is because industry concentration is essentially a massive drag. As a result, corporate profits will increase. This study aims to analyze and find out how the market structure and performance of the textile industry and products (TPT) through the Structure-Conduct-Performance approach. The data collection method in this research is descriptive quantitative method with panel data regression analysis. The objects observed in this study are Market Share (MS), Concentration Ratio (CR4), Minimum Efficiency Scale (MES), Capital Labor Ratio (CLR), Internal Efficiency (XEF) and Price Cost Margin (PCM). Based on the results of the analysis obtained that the variable that has the greatest and significant influence in improving performance is efficiency (XEF).